2021
DOI: 10.2147/sar.s296526
|View full text |Cite
|
Sign up to set email alerts
|

Antisocial Personality Disorder Among Patients in Treatment for Alcohol Use Disorder (AUD): Characteristics and Predictors of Early Relapse or Drop-Out

Abstract: Background: Patients with alcohol use disorders (AUD) vary significantly in many clinically important characteristics making them a heterogenous group. AUD patients with comorbid antisocial personality disorder (ASPD) form an important sub-group, and studies indicate that these patients may have poorer treatment outcomes. Therefore, we aimed to investigate the characteristics of AUD inpatients with comorbid ASPD and identify predictors of early relapse or treatment drop-out in these patients. Methods: In a lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
2
0
2
Order By: Relevance
“…Antisocial and borderline personality pathologies are prominent in relation to relapse in SUD, but data are limited and randomized controlled studies with more extended follow-up periods are needed. 18 Similarly, in a study conducted in alcohol dependence, antisocial personality disorder was found to increase the risk of relapse; 53 some studies have not found this relationship. 13 …”
Section: Clinical and Research Consequencesmentioning
confidence: 98%
“…Antisocial and borderline personality pathologies are prominent in relation to relapse in SUD, but data are limited and randomized controlled studies with more extended follow-up periods are needed. 18 Similarly, in a study conducted in alcohol dependence, antisocial personality disorder was found to increase the risk of relapse; 53 some studies have not found this relationship. 13 …”
Section: Clinical and Research Consequencesmentioning
confidence: 98%
“…Opptil 67 % av AUD-pasienter skårer høyt på personlighetstrekket aleksitymi, som innebaerer vansker med følelsesbevissthet ogregulering, og gruppen med disse utfordringene hadde mer alvorlig avhengighet (Thorberg et al, 2019). En ny norsk studie av norske AUD-pasienter ved tre behandlingsinstitusjoner fant at 15 % av pasientene fylte kriteriene for ASPF, men at ASPF ikke predikerte frafall eller tilbakefall (Pandey et al, 2021). Denne studien hadde relativt få pasienter med ASPF, men er interessant fordi den ble gjennomført på en norsk AUD-populasjon.…”
Section: Personlighetsproblemerunclassified
“…Opptil 67 % av AUD-pasienter skårer høyt på personlighetstrekket aleksitymi, som innebaerer vansker med følelsesbevissthet og -regulering, og gruppen med disse utfordringene hadde mer alvorlig avhengighet (Thorberg et al, 2019). En ny norsk studie av norske AUD-pasienter ved tre behandlingsinstitusjoner fant at 15 % av pasientene fylte kriteriene for ASPF, men at ASPF ikke predikerte frafall eller tilbakefall (Pandey et al, 2021). Denne studien hadde relativt få pasienter med ASPF, men er interessant fordi den ble gjennomført på en norsk AUD-populasjon.…”
Section: Personlighetsproblemerunclassified